Latent approaches for unsupervised learning-based methodologies in gearbox fault diagnosis applications - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2024)
Thesis (PhD (Mechanical Engineering))--University of Pretoria, 2024.